Novel post‐tensioned rocking piles for enhancing the seismic resilience of bridges. (2nd November 2021) - El‐Hawat, Omar; Fatahi, Behzad; Taciroglu, Ertugrul
Abstract: The rocking pile foundation system is a relatively new design concept that can be implemented in bridges to improve their seismic performance. This type of foundation prevents plastic damage at the bridge piers and the foundation system, which are difficult to repair and can lead to collapse. However, lack of adequate energy dissipation in this type of foundation can result in large deck displacements and subsequent catastrophic failures of the bridge. The present study proposes a novel foundation system that integrates post‐tensioned piles with the rocking foundation to simultaneously prevent plastic hinging at the piers and reduce the deck displacements during severe earthquakes. The effectiveness of the proposed foundation system is investigated and compared against the rocking pile and conventional fixed‐base foundation systems using identical bridge configurations. Three‐dimensional finite element models of these bridges were developed to capture possible nonlinear behavior of the bridge as well as soil‐structure interaction effects. Six strong earthquakes with both horizontal components were selected and scaled to the appropriate seismic hazard level with a return period of 2475 years. Static pushover and nonlinear time‐history analyses were then performed to compare the dynamic response of the bridges, including deck displacements, pier and pile inertial forces, and other nonlinear behavior experienced by the structure. The results reveal that by integrating the post‐tensioned piles with the rocking foundation, the deck displacements were reduced to an acceptable limit without subjecting the bridge to any damage. In contrast, the bridge with the fixed base foundation experienced extensive damage at the piers, and the bridge with the rocking foundation experienced substantial deck displacements that ultimately led to unseating, resulting in the collapse of both bridges. It was therefore concluded that the proposed rocking foundation system with post‐tensioned piles is the superior alternative and can be implemented in practice as an attractive solution due to the seismic protection it offers.